Associations between acute glucose control and peripheral nerve structure and function in type 1 diabetes. Issue 9 (17th May 2020) - Issar, T.; Tummanapalli, S. S.; Kwai, N. C. G.; Chiang, J. C. B.; Arnold, R.; Poynten, A. M.; Markoulli, M.; Krishnan, A. V.
Abstract: Aim: To examine the associations between continuous overlapping net glycaemic action (CONGA), percentage time in hyperglycaemia (%HG) or normoglycaemia (%NG) and peripheral nerve structure and function in type 1 diabetes. Methods: Twenty‐seven participants with type 1 diabetes underwent continuous glucose monitoring followed by corneal confocal microscopy and nerve excitability assessments. CONGA, %HG (> 10.0 mmol/l) and %NG (3.9–10.0 mmol/l) were correlated against corneal nerve fibre length and density in the central cornea and inferior whorl region, corneal microneuromas, and a nerve excitability score while controlling for age, sex, diabetes duration and HbA1c . Results: An increase in CONGA [median 2.5 (2.0–3.1) mmol/l] or %HG (mean 46 ± 18%) was associated with a worse nerve excitability score ( r = –0.433, P = 0.036 and r = –0.670, P = 0.0012, respectively). By contrast, greater %NG (51 ± 17%) correlated with better nerve excitability scores ( r = 0.672, P = 0.0011). Logistic regression revealed that increasing %HG increased the likelihood of abnormal nerve function [odds ratio (OR) 1.11, 95% confidence interval (CI) 1.01–1.23; P = 0.037). An increase in CONGA and %HG were associated with worsening nerve conduction measures, whereas longer %NG correlated with improved nerve conduction variables. CONGA and %HG were associated with inferior whorl corneal nerve fibre length ( r = 0.483, P = 0.034 and r = 0.591, P = 0.021, respectively) and number of microneuromas ( r = 0.433, P = 0.047 and r = 0.516, P = 0.020, respectively). Conclusions: Short‐term measures of glucose control are associated with impaired nerve function and alterations in corneal nerve morphology. What's new?: Acute measures of glucose control have been associated with retinopathy and microalbuminuria, but their relationship with neuropathy requires exploration. Greater glucose variability and percentage time above range was associated with worsening nerve function. Higher percentage time in range was correlated with better nerve function. Increasing glucose variability and time above range was associated with greater corneal nerve length in the inferior whorl and higher counts of microneuromas. Monitoring of acute measures of glucose control may have more utility than HbA1c in the prevention of diabetic neuropathy.